PERAWATAN PLUNGING RANULA DENGAN PEMBUKAAN DARI INTRAORAL DAN EKSTRAORAL - Melva Novi Yanti; Herman Hambali; Winarno Priyanto; Kiki A Riski (Journal of Syiah Kuala Dentistry Society, 2017)
Plunging ranula is a mucous extravasation pseudocyst which arises from the sublingual gland and crosses the mylohyoid line into the neck, usually appear in conjunction with oral ranula. To evaluate that the early diagnosis and proper surgical procedure can decreased recurrences rate. A 25 year old man visited Department of Oral Surgery Hasan Sadikin Hospital because of a fluctuant swelling of the left submandibular region and swelling of floor of the mouth. A sonography revealed there was a cystic mass at left submandible and not related to left parotis gland and thyroid. There was enlargment of multiple gland at left neck. The clinical diagnosis was plunging ranula. This case was treated with marsupialization and extirpation of the mass included removal of sublingual salivary gland. Postoperatively, one week after surgery the swelling was reduced and there was no more pain and paresthesia. Many patients have experienced recurrence and sometimes larger lesions have occurred. Excision of the ranula with the associated sublingual salivary gland is the most accepted method with low recurrence rate. It is a case of a 25 year old male presented with plunging ranula with both the oral and submandibular component and its removal by combined intraoral and ekstraoral approach has been reported with no recurrence after a follow up of one mounth.Keyword: Plunging ranula, sublingual gland, mucous extravasation